2021
DOI: 10.1021/acs.orglett.1c01922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Biomimetic Tetracyclic Precursor of Aspochalasins and Formal Synthesis of Trichoderone A

Abstract: Aspochalasins are leucine-derived cytochalasins. Their complexity is associated to a high degree of biosynthetic oxidation, herein inspiring a two-phase strategy in total synthesis. We thus describe the synthesis of a putative biomimetic tetracyclic intermediate. The constructive steps are an intramolecular Diels-Alder reaction to install the isoindolone core of cytochalasins, whose branched precursor was obtained from a stereoselective Ireland-Claisen rearrangement performed from a highly unsaturated substrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…This journal is © The Royal Society of Chemistry 2024 Methyl (1S,3aR,4S,7S,7aR)-6,7-dimethyl-3-oxo-1-( phenanthren-9-ylmethyl)-4-(2-phenethoxyethyl)-1,2,3,4,7,7a-hexahydro-3aH-isoindole-3a-carboxylate (26). By following the general procedure, the cross-coupling reaction was carried out with Fe (acac) 3 (38 mg, 108 µmol), 19 (50 mg, 108 µmol) in dry THF…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 1 more Smart Citation
“…This journal is © The Royal Society of Chemistry 2024 Methyl (1S,3aR,4S,7S,7aR)-6,7-dimethyl-3-oxo-1-( phenanthren-9-ylmethyl)-4-(2-phenethoxyethyl)-1,2,3,4,7,7a-hexahydro-3aH-isoindole-3a-carboxylate (26). By following the general procedure, the cross-coupling reaction was carried out with Fe (acac) 3 (38 mg, 108 µmol), 19 (50 mg, 108 µmol) in dry THF…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…Since their discovery, chemists have been pursuing the total synthesis of cytochalasans due to their intricate structure, which poses a persistent challenge. [25][26][27][28][29] However, none of the total syntheses have involved the late-stage introduction of substituents into position 10, so far. Only a synthesis of cytochalasan analogues based on desymmetrization reactions of succinimide derivatives has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their biologically active nature, efforts towards their total synthesis were inevitable. Gayraud et al [ 75 ] in 2021 reported the total synthesis of these cyclic cytochalasin natural products, i.e., aspochalasins, leading to the synthesis of trichoderone. Their synthetic approach included Sharpless asymmetric dihydroxylation, Ireland–Claisen rearrangement, Diels–Alder reaction and Suzuki–Miyaura cross-coupling reaction as the main steps.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…By taking advantage of this biomimetic transformation, Nay and co-workers achieved the formal synthesis of trichoderone A through a “cyclase-oxidase” two-phase strategy in 2021 (Scheme 9). 23 In the “cyclase” phase, they synthesized the key tetracyclic intermediate 95 through an Ireland–Claisen rearrangement and an intramolecular Diels–Alder reaction.…”
Section: Total Synthesis Of Cytochalasansmentioning
confidence: 99%